Analysis of high school students’ awareness of the psychosocial effects of internet addiction - M. Dawood, Roaa; A. Yasir, Amean (Edelweiss Applied Science and Technology, 2024)
The present study aims to determine secondary school students’ awareness of the psychosocial consequences of Internet addiction and to investigate differences in the level of awareness based on students’ sociodemographic characteristics (Sex, grade level, number of family members, parent’s marital status, education and occupation of the parents, and the family’s monthly income). A cross-sectional descriptive study was conducted from December 10, 2022, to December 30, 2023. The sample included (765) secondary school students were (375 males and 390 females). The population was composed of 10th and 12th grade students withdrawn from ten high schools located in the Babylon Governorate in Iraq. The results of the study revealed a variation in participants’ awareness of their knowledge of the psychosocial effects of Internet addiction, as more than half of them (57.5%) recorded a fair level of awareness, while (40.1%) of them recorded a good level, and only (2.4%) exhibited a waek level of awareness. Furthermore, the data revealed notable gender and grade-level differences in psychosocial awareness. Females exhibited a higher level of awareness (51.5%) compared to males. Additionally, students in the 10-grade showed a relatively higher rate of good psychosocial awareness (44.9%). It is necessary to understand the demographic factors in shaping awareness of the effects of Internet addiction, which helps in developing targeted intervention strategies to enhance awareness and improve students’ control behaviors.